The Use of Natural Material Media to Develop the Creativity of Children Aged 5–6 Years - Eka Pratiwi; I. Ismail (Golden Ratio of Data in Summary, 2026)
Creativity is an important aspect that needs to be developed in early childhood education. However, in kindergarten learning activities, the development of children's putrabangsacreativity is often limited due to the lack of varied learning media. One alternative learning media that can be used is natural materials that are easily found in the surrounding environment. This study aims to determine the use of natural materials to develop the creativity of kindergarten children putrabangsa. This study used Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of the research were 13 children in group B of kindergarten. Data collection techniques included observation, documentation, and field notes. Data were analyzed descriptively to determine the improvement of children's creativity during the learning process. The results showed that the use of natural materials improved children's creativity. Children became more active and enthusiastic and were able to express their ideas and imagination through various works made from natural materials such as leaves, twigs, and seeds. Therefore, natural materials can be used as effective learning media to develop creativity in kindergarten children.